EPIDEMIOLOGICAL INVESTIGATION OF THE CLINICAL MANIFESTATION OF BISPHOSPHONATE-ASSOCIATED OSTEONECROSIS OF THE JAWS IN 112 ONCOLOGY PATIENTS - Meri Hristamyan; Ralitsa Raycheva; Veselka Hristamyan (Journal of IMAB, 2025)
Background: Bisphosphonate-associated osteonecrosis of the jaws (BAONJ) is a condition linked to the intake of Bisphosphonates (BP) and clinically manifesting in mucosal ulceration and exposure of underlying necrotic bone. The aim of the study is to analyze the clinical manifestation, paraclinical methods for diagnosis, and treatment methods of BAONJ in oncology patients. Methods: A prospective epidemiological study of 112 oncology patients diagnosed with BAONJ was conducted in the Clinic of maxillo-facial surgery of UMHAT "St. George", Plovdiv, Bulgaria. SPSS Statistics v.24 was used for statistical analysis at a significance level of p<0.05. Results: The main diagnostic methods were clinical examination and history taking, with X-rays in 91.96% (n=103). Half of the patients were diagnosed at stage II, 29.46% at stage I, 17.86% at stage III, and 1.79% at stage 0. The highest proportion of patients (71.41%, n=80) reported pain in the jaws, about 2/3 - exposed bone (65.18%, n=73), and swelling/edema (60.71%, n=68). Treatment included an antibiotic in 54.45% (n=61) of the β-lactam antibiotics group. Debridement was performed in 32.14% (n=36) of cases, followed by other surgical manipulation in 18.75% (n=21) and resection in 4.56% (n=5). Conclusion: BAONJ is diagnosed late, which leads to the necessity of surgical treatment.